Safety practices related to small fishing vessel stability - Gudmundsson, Ari (FAO RomeIT, 2009)
Deals with some basic principles on the stability of small fishing vessels. Provides simple guidance on what fishing vessel crews can do to maintain adequate stability for their vessels.